Penguatan Mobilitas dan Urban Planning di Kota Makassar: Solusi Kebijakan untuk Lingkungan dan Ketahanan Kota Akibat Risiko Bencana - Ambo Masse; Muhammad Wahyudi Mokobombang (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
The urgency of this research lies in the increasing risk of flooding and air pollution in Makassar City due to rapid urbanisation and the uncontrolled growth of motorised vehicles. The purpose of this study is to analyse the potential of urban planning and sustainable mobility policies in reducing disaster risks and environmental impacts, and to formulate more adaptive and data-driven policy strategies. This study uses qualitative methods by collecting data through interviews, documentation, observation, and focus group discussions (FGDs). Key informants include the Environmental Agency, the Spatial Planning Agency, and the Makassar Regional Disaster Management Agency (BPBD), which have strategic roles in spatial planning policies, environmental management, and disaster mitigation. The study findings indicate that flood risk and air pollution in Makassar City are complex problems influenced by population growth, land conversion, vehicle density, limited drainage, climate change, and industrial waste. Although various urban planning policies have been implemented, their effectiveness remains limited due to implementation constraints. Therefore, an integrated approach that combines adaptive urban planning, environmentally friendly mobility, effective waste management, and community participation is needed. With a systemic and coordinated strategy, Makassar has the potential to reduce flood risk, reduce pollution, and create a safer, healthier, and more sustainable urban environment.